Implementation of a Levitation System for the Visualization of the Magnetic Phenomenon - Zeila Torres Santos; Brian Meneses-Claudio (Advances in Science, Technology and Engineering Systems Journal, 2020)
The phenomenon of magnetic fields is affected depending on the polarity, the positive and negative poles will give a response of attraction and repulsion that can be easily observed. Being also important as an educational element where the theory materializes and is observed, which enriches all science. The objective of this work is to create a circuit that allows reaching the balance between the electronic components, making use of the fundamental electronics together with an LDR and a light sensor. Both generate a connection bridge in which the object that levitates to remain in the air fluctuates, achieving the objective of creating a levitator and being able to observe the nature of electronics and electromagnetism as a whole. As a result, it was obtained that there is a difference between the use of basic and advanced electronic circuits, in addition to identifying the variation in the voltage consumption between the coin and the screw, because the more voltage consumption, the greater the length of wave implying that the frequency decreases but the power intensifies. On the other hand, it should be noted that the use of a voltage generator to identify the voltage and power variations that were shown at the time of the different tests.
Keywords: Magnetic Levitator; Electromagnet; Electronic Circuit; Differential Potential